Public investment and growth accelerations: The case of Southern Italy, 1951-1995 - Erasmo Papagni; Amedeo Lepore; Emanuele Felice; Anna Laura Baraldi; Maria Rosaria Alfano (Economics and Econometrics Research Institute (EERI), 2018)
This paper analyses the contribution of public investment to growth in southern Italy in the second half of the twentieth century (1951-1995). The period saw the only convergence in modern times of the Mezzogiorno towards the Italian average (1951-1973), followed by divergence (1974-1995). Using cointegration analysis we find a statistically significant positive effect of public investment on the growth of the Mezzogiorno in the period 1951-1995. The Bai-Perron tests suggest that economic growth followed two distinct regimes, the first regime of accelerated growth in the years 1951-1973 (average growth rate 5.3%), and the second regime of low growth in the period 1974-1995 (average growth rate 1.6%). This result is confirmed by the testing procedure of Hansen (1992) which indicates a break in the determinants of GDP per unit of labour in 1974. The estimates of the model on time series of the two periods show statistically significant parameters of public investment in the first regime, but not in the second regime, when economic growth is sustained by business investment and technical change. The paper suggests that public capital may have a significant positive role in episodes of growth accelerations if the quality of the institutional environment is high, but it can lose its effectiveness if bureaucratic corruption and rent-seeking strongly affect public policy.
Keywords: H54; O14; O18; O47; 330; Public Investment; Growth Instability; Cointegration; Structural breaks; Southern Italy